Neutrophil extracellular traps contribute to the pathogenesis of leprosy type 2 reactions. - Camila Oliveira da Silva; André Alves Dias; José Augusto da Costa Nery; Alice de Miranda Machado; Helen Ferreira; Thais Fernanda Rodrigues; João Pedro Sousa Santos; Natalia Rocha Nadaes; Euzenir Nunes Sarno; Elvira Maria Saraiva; Verônica Schmitz; Maria Cristina Vidal Pessolani (Public Library of Science (PLoS), 2019)
Up to 50% of patients with the multibacillary form of leprosy are expected to develop acute systemic inflammatory episodes known as type 2 reactions (T2R), thus aggravating their clinical status. Thalidomide rapidly improves T2R symptoms. But, due to its restricted use worldwide, novel alternative therapies are urgently needed. The T2R triggering mechanisms and immune-inflammatory pathways involved in its pathology remain ill defined. In a recent report, we defined the recognition of nucleic acids by TLR9 as a major innate immunity pathway that is activated during T2R. DNA recognition has been described as a major inflammatory pathway in several autoimmune diseases, and neutrophil DNA extracellular traps (NETs) have been shown to be a prime source of endogenous DNA. Considering that neutrophil abundance is a marked characteristic of T2R lesions, the objective of this study was to investigate NETs production in T2R patients based on the hypothesis that the excessive NETs formation would play a major role in T2R pathogenesis. Abundant NETs were found in T2R skin lesions, and increased spontaneous NETs formation was observed in T2R peripheral neutrophils. Both the M. leprae whole-cell sonicate and the CpG-Hlp complex, mimicking a mycobacterial TLR9 ligand, were able to induce NETs production in vitro. Moreover, TLR9 expression was shown to be higher in T2R neutrophils, suggesting that DNA recognition via TLR9 may be one of the pathways triggering this process during T2R. Finally, treatment of T2R patients with thalidomide for 7 consecutive days resulted in a decrease in all of the evaluated in vivo and ex vivo NETosis parameters. Altogether, our findings shed light on the pathogenesis of T2R, which, it is hoped, will contribute to the emergence of novel alternative therapies and the identification of prognostic reactional markers in the near future.